Patrick Russell (1727–1805), surgeon and polymath naturalist - Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust., 2015)
The life and times of Patrick Russell (1727–1805), a Scottish medical practitioner and natural historian from Edinburgh, are traced, with emphasis on his work in the Ottoman town of Aleppo (currently, Halab, in north-western Syria), with that of his halfbrother, Alexander Russell (1715–1768), and along the Coromandel Coast (in eastern India). Russell is best known amongst zoologists for the discovery of his namesake, the venomous serpent referred to as Russell’s Viper, Daboia russelii. His two folio volumes, centred around his time in the Coromandel coast of south-eastern India, was lavish in its illustrations of Indian snakes, and executed by an unknown Indian artist. Vernacular, rather than English or scientific names were used in this compendium, arguably the first text exclusively on a herpetological topic published on the Indian fauna. Apart from snakes commonly occurring in the south-eastern India, the work also describes a few species sent to Russell by colleagues from other parts of Asia. He also experimented on the venom of the local snakes, and documented their effects on dogs, rabbits and chickens,these being the first attempts to classify the venomous snakes from the harmless ones in the country.